Ammonia stripping using a continuous flow jet loop reactor: mass transfer of ammonia and effect on stripping performance of influent ammonia concentration, hydraulic retention time, temperature, and air flow rate - Değermenci, Nejdet; Yildiz, Ergun (Springer Science and Business Media LLC, 2021)
When wastewater containing ammonia is discharged into the receiving environment without any kind of treatment, it causes both environmental problems and negatively affects human health. In this study, the aim was to strip ammonia using air in a continuous flow jet loop reactor (JLR) and investigate the effects of ammonia concentration, hydraulic retention time (HRT), air flow rate, and temperature on ammonia removal within this scope. By changing the ammonia concentration in the influent, no significant change was observed in ammonia removal efficiency. With air flow rate 45 L min-1, temperature 50 °C, pH 11, and HRT 7.5 h, mean 88.1% ammonia removal was achieved. Increasing the HRT, air flow rate, and temperature increased the ammonia removal efficiency. Later the ammonia stripping process in the continuous flow JLR was modeled and the volumetric mass transfer coefficient (KLa) for each parameter was calculated from the model equation. While the experimental parameters of air flow rate and temperature had a significant effect on the mass transfer coefficient, influent ammonia concentration and HRT were determined to have no effect.
Keywords: Bioreactors; Ammonia; Nitrogen; Temperature; Humans; Wastewater; Waste Disposal, Fluid; 6. Clean water; 12. Responsible consumption